Ground improvement techniques - Huat, Bujang B. K. (Leiden, The Netherlands : CRC Press/Balkema, 2020)
This book provides a review of problems during design and construction on problematic soils. Design methods, site investigation, construction and analysis of the various improvement methods available are explained and discussed. Various regions may have different soils with geotechnical problems that differ from those faced in other regions. For example, in Southeast Asia, the common geotechnical problems are those associated with construction on soft clays and organic soils, while in the arid region of the Middle East, problems are generally associated with the desert soils. In the US, the problems are associated with organic soils, expansive and collapsing soils, and shale. Laterite and lateritic soils are especially problematic in Mexico. Similarly, in Europe, for example, the geotechnical problems are associated with loess (France), and organic soil (Germany). A detailed description of various methods of ground improvement has been provided in 11 chapters. Each chapter deals not only with a description of the method but also focuses on region-specific ground problems and suitable ground improvement techniques. Case studies have also been included. One general chapter is dedicated to site investigation, instrumentation, assessment and control. This book will be of value to students and professionals in the fields of civil and geotechnical engineering, as well as to soil scientists and engineering geologists.
OCLC-licensed vendor bibliographic record.
Keywords: TECHNOLOGY / Engineering / Civil; Soil mechanics; Soil stabilization; Soil consolidation